2001
DOI: 10.1042/cs1010593
|View full text |Cite
|
Sign up to set email alerts
|

Differential roles of nitric oxide and oxygen radicals in chondrocytes affected by osteoarthritis and rheumatoid arthritis

Abstract: Osteoarthritis and rheumatoid arthritis are characterized by focal loss of cartilage due to an up-regulation of catabolic pathways, induced mainly by pro-inflammatory cytokines, such as interleukin-1 (IL-1) and tumour necrosis factor alpha (TNFalpha). Since reactive oxygen species are also involved in this extracellular-matrix-degrading activity, we aimed to compare the chondrocyte oxidative status responsible for cartilage damage occurring in primarily degenerative (osteoarthritis) and inflammatory (rheumatoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(49 citation statements)
references
References 14 publications
5
42
0
2
Order By: Relevance
“…We found elevated MnSOD mRNA expression in chondrocytes after TGF-β1 induction. This findings is in line with results from Mazzetti et al who reported up-regulation of intracellular MnSOd in osteoarthritic chondrocytes in response to several cytokines; this up-regulation was interpreted as a compensatory reaction to the higher nitric oxide levels in osteoarthritis chondrocytes compared to rheumatoid arthritis chondrocytes (29). Moreover, superoxide dismutase has been shown to effectively prevent interleukin-1β IκBα degradation and, thus, inhibit inducible nitric oxide synthase (iNOS) expression (30), as well as production of ROS induced by tensile stress (31).…”
Section: Discussionsupporting
confidence: 82%
“…We found elevated MnSOD mRNA expression in chondrocytes after TGF-β1 induction. This findings is in line with results from Mazzetti et al who reported up-regulation of intracellular MnSOd in osteoarthritic chondrocytes in response to several cytokines; this up-regulation was interpreted as a compensatory reaction to the higher nitric oxide levels in osteoarthritis chondrocytes compared to rheumatoid arthritis chondrocytes (29). Moreover, superoxide dismutase has been shown to effectively prevent interleukin-1β IκBα degradation and, thus, inhibit inducible nitric oxide synthase (iNOS) expression (30), as well as production of ROS induced by tensile stress (31).…”
Section: Discussionsupporting
confidence: 82%
“…Several studies have shown that ROS are involved in the degradation of the extracellular matrix of articular cartilage (Mazetti et al 2001) and the suppression of proteoglycan synthesis (Bates et al 1984;Schalwijk et al 1985;Tiku et al 1999). Superoxide radicals, generated enzymatically by the action of xanthine oxidase on hypoxanthine, significantly reduce proteoglycan synthesis of cultured bovine articular cartilage as demonstrated by 35 S-sulphate incorporation (Bates et al 1984).…”
Section: Membrane Damagementioning
confidence: 96%
“…Neutrophil derived reactive oxygen intermediates, such as hydrogen peroxide and superoxide radicals, are responsible for the pathogenesis of various inflammatory conditions (Halliwell, 1994;Gafvert et al, 2002;Mazzetti et al, 2001;Hanson and Clegg, 2002;Loukides et al, 2002). The antiinflammatory properties of various medicinal plant extracts have been explained, at least in part, by their antioxidant activities (Gerritsen et al, 1995;Gali-Muhtasib et al, 1999;Schinella et al, 2002;Lindsey et al, 2002).…”
Section: Introductionmentioning
confidence: 97%